2020
DOI: 10.1111/hel.12688
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication treatment and the risk of Barrett's esophagus and esophageal adenocarcinoma

Abstract: Background Helicobacter pylori (H. pylori) is associated with lower risks of Barrett's esophagus and esophageal adenocarcinoma, but whether H. pylori eradication increases the risk of these conditions is unknown. This study aimed to test the hypothesis that H. pylori eradication leads to gradually increased risks of Barrett's esophagus and esophageal adenocarcinoma over time, while esophageal squamous cell carcinoma was assessed for comparison reasons. Material and Methods This Swedish nationwide, population‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
1
20
0
3
Order By: Relevance
“…For example, because eradication of H. pylori infection can restore or improve gastric acid secretion, it has been postulated that it may increase acid reflux to the oesophagus and even lead to an increase in oesophageal adenocarcinoma. 14 Antibiotic treatment also has the potential to disrupt the gut microbiota, which might produce unknown consequences. 15 Finally, there is concern regarding its effect on global antimicrobial resistance or emergence of antibiotic-resistant strains of H. pylori.…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…For example, because eradication of H. pylori infection can restore or improve gastric acid secretion, it has been postulated that it may increase acid reflux to the oesophagus and even lead to an increase in oesophageal adenocarcinoma. 14 Antibiotic treatment also has the potential to disrupt the gut microbiota, which might produce unknown consequences. 15 Finally, there is concern regarding its effect on global antimicrobial resistance or emergence of antibiotic-resistant strains of H. pylori.…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…Six meta-analyses on association of HPI and esophageal adenocarcinoma indicated an inverse relationship [ 238 ], whereas a recent meta-analysis (35 studies including 345,886 patients) did not find such association, except the Middle East data [ 239 ]. Other researchers concluded that presence of HPI might aggravate GERD [ 240 ], or, at least, is not “protective” against GERD, as the incidence of GERD and its sequelae in patients with HPI is higher than that after eradication of the infection [ 241 , 242 ], HPI eradication improves GERD symptoms and esophagitis [ 243 , 244 , 245 , 246 , 247 ] and does not increase the risk of BO [ 248 , 249 , 250 ]. Meta-analyses on effect of eradication HPI produced, however, inconsistent results [ 229 ]: a significantly higher risk of developing de novo GERD was demonstrated in Asian studies [ 251 ], but not in Western ones [ 252 , 253 , 254 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…The SIRs of esophageal squamous cell carcinoma (n = 10) were not influenced by eradication treatment. The authors conclude that there is no evidence of an increased risk of Barrett's esophagus or esophageal cancer after H pylori eradication treatment 5 . Furthermore, a Brazilian cohort was analysed retrospectively to determine the impact of H pylori infection on the development of Barrett's esophagus.…”
Section: Esophageal Diseasesmentioning
confidence: 98%